Effect of carbon black substitution with modified and raw bentonite on the properties of natural rubber composites - Garing, Clare L.; Pajarito, Bryan B. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The effect of carbon black (CB) substitution with modified (M-BNT) and raw (BNT) bentonite on the properties of natural rubber (NR) composites was investigated in this study. NR composites were prepared using a third degree simplex lattice mixture design of experiment wherein proportions of CB, M-BNT, and BNT were varied in the rubber formulations. M-BNT was produced by modifying sodium-activated bentonite with tetradecyl dimethylamine (TDA) salt and cocamide diethanolamine (CDEA). Results of Fourier transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD) analysis and scanning electron microscopy (SEM) confirmed the efficiency of the two-step organic modification performed on BNT. Synergistic effect on the curing, mechanical and aging properties of NR composites was observed on NR composite 10/5/0 due to formation of a dual-filler structure. The difference in the reinforcing effect of BNT and M-BNT was due to the incompatibility of BNT with natural rubber. Furthermore, improvement of properties after CB replacement with M-BNT was attributed to the good rubber-filler interaction as a result of clay modification. Introduction of clay fillers in the polymer matrix increased the thermal aging resistance of NR composites due to the platelet structure of clays. Replacement of CB up to 5phr of clay fillers gave pronounced enhancement in the water diffusion properties of NR composites. Contour plots were generated based on reduced hierarchical models which mostly demonstrated synergy between CB and M-BNT as well as inferiority of BNT filler.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman
Keywords: Bentonite; Carbon-black.; Rubber